Review of EPA's Updated Problem Formulation and Protocol for the Inorganic Arsenic IRIS Assessment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The Integrated Risk Information System (IRIS) is a program within the US Environmental Protection Agency (EPA) that is responsible for developing toxicologic assessments of environmental contaminants. An IRIS assessment contains hazard identifications and dose-response assessments of various chemicals related to cancer and noncancer outcomes. Although the program was created to increase consistency among toxicologic assessments within the agency, federal, state, and international agencies and other organizations have come to rely on IRIS assessments for setting regulatory standards, establishing exposure guidelines, and estimating risks to exposed populations. The EPA has been working on its IRIS assessment of inorganic arsenic (iAs) for many years, and recently released its plans for completing it in the Updated Problem Formulation and Protocol for the Inorganic Arsenic IRIS Assessment. Much of the update was made in response to recommendations in a 2013 report made by the National Academies of Sciences, Engineering, and Medicine. The National Academies recently convened another evaluation of whether the various elements of the IRIS iAs assessment plan are appropriate to synthesize the scientific evidence and quantitate estimates of iAs toxicity. Review of EPA’s IRIS Assessment Plan for Inorganic Arsenic explores the EPA’s approach to prioritizing health outcomes, EPA’s systematic review methods, EPA’s consideration of potential health effects from early life exposures, mode-of-action information to inform dose-response analyses, and various approaches to investigate dose-response relationships.
Keywords: Environment and Environmental Studies

Review of the Final Draft Analysis of Supplemental Treatment Approaches of Low-Activity Waste at the Hanford Nuclear Reservation: Review #3 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In 1943, as part of the Manhattan Project, the Hanford Nuclear Reservation was established with the mission to produce plutonium for nuclear weapons. During 45 years of operations, the Hanford Site produced about 67 metric tonnes of plutonium—approximately two-thirds of the nation's stockpile. Production processes generated radioactive and other hazardous wastes and resulted in airborne, surface, subsurface, and groundwater contamination. Presently, 177 underground tanks contain collectively about 210 million liters (about 56 million gallons) of waste. The chemically complex and diverse waste is difficult to manage and dispose of safely.
Keywords: Environment and Environmental Studies

Review and Update of U.S. Coast Guard Vessel Stability Regulations and Guidance - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
U.S. Coast Guard (USCG) ship stability regulations governing the ability of a vessel to return to an upright position after being disturbed is the focus of a new TRB publication, Review and Update of U.S. Coast Guard Vessel Stability Regulations and Guidance. The authors advise the USCG on how it can make its stability regulations more usable and complete in meeting the requirements of different types of vessels and those vessels that have undergone weight changes that can affect their stability characteristics.The USCG has safety regulatory jurisdiction over vessels registered in the United States. One of its oldest regulatory functions is to ensure these ships, boats, and other floating vessels remain upright as they encounter both expected and unexpected loading, operating, and weather conditions, including wind and wave conditions and unexpected failure of watertight integrity.Stability standards have been improved over time - particularly in the past 30 years - and the USCG remains keenly interested in making sure the regulations are kept updated based on the latest technical knowledge, well aligned with international standards, and organized and presented in a manner that facilitates compliance and enforcement. The recommendations in the report are intended to further these aims. The USCG earlier commissioned a National Academies study to identify options for improving vessel stability regulations, and after receiving that study in September 2018, the USCG asked for this second study to provide more in-depth advice on applying these options.
Keywords: Transportation and Infrastructure

Integrating Sustainability Planning and the Environmental Review Process - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Environmental regulations have long required airports to undertake review of many actions associated with planning and development. More recently, airports have embraced sustainability as a means for ensuring the long-term viability and community benefits of their facilities.The TRB Airport Cooperative Research Program's ACRP Research Report 209: Integrating Sustainability Planning and the Environmental Review Process is designed for airport industry practitioners who are interested in gaining a better understanding of the benefits of integrating environmental review with sustainability planning, and who would like strategies and tools to help them implement this integration.While there remain challenges to integrating environmental review and sustainability, this report should help guide practitioners on the many opportunities for integration and alignment.
Keywords: Transportation and Infrastructure

Review of DOD's Approach to Deriving an Occupational Exposure Level for Trichloroethylene - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Trichloroethylene (TCE) is a solvent that is used as a degreasing agent, a chemical intermediate in refrigerant manufacture, and a component of spot removers and adhesives. It is produced in mass quantities but creates dangerous vapors and is an environmental contaminant at many industrial and government facilities, including facilities run by the U.S. Department of Defense (DoD). It is important to determine the safe occupational exposure level (OEL) for the solvent in order to protect the health of workers who are exposed to its vapors. However, there are concerns that the current occupational standards insufficiently protect workers from these health threats.
Keywords: Environment and Environmental Studies

Committee on Human Rights: Year in Review 2018 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The annual report of the Committee on Human Rights (CHR) provides an overview of the CHR's activities in 2018, including information on its advocacy, events, and awareness-raising projects.
Keywords: Behavioral and Social Sciences

2018 Year in Review: Roundtable on Obesity Solutions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Keywords: Food and Nutrition

2018 Year in Review: Roundtable on Population Health Improvement - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Keywords: Health and Medicine

A Research Review of Interventions to Increase the Persistence and Resilience of Coral Reefs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Coral reef declines have been recorded for all major tropical ocean basins since the 1980s, averaging approximately 30-50% reductions in reef cover globally. These losses are a result of numerous problems, including habitat destruction, pollution, overfishing, disease, and climate change. Greenhouse gas emissions and the associated increases in ocean temperature and carbon dioxide (CO2) concentrations have been implicated in increased reports of coral bleaching, disease outbreaks, and ocean acidification (OA). For the hundreds of millions of people who depend on reefs for food or livelihoods, the thousands of communities that depend on reefs for wave protection, the people whose cultural practices are tied to reef resources, and the many economies that depend on reefs for fisheries or tourism, the health and maintenance of this major global ecosystem is crucial.
Keywords: Earth Sciences

Review of the Draft 2019 Science Mission Directorate Science Plan - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
NASA’s Science Mission Directorate (SMD) ties together diverse researchers, sponsors, and resources to develop the science community’s understanding of the universe. Within scientific organizations like NASA, it is important to establish clear strategies and goals to guide research and foster new discoveries across varying missions. SMD created a draft for their 2019 Science Plan, and a review of this draft is necessary to ensure that the plan establishes clear, attainable, relevant, and ambitious goals.
Keywords: Space and Aeronautics

Pedestrian Safety Relative to Traffic-Speed Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Measures that are effective at reducing speed, such as speed humps and mini traffic circles, are sometimes used in low-speed areas such as school zones. But they are often not recommended or allowed (via local policy) on the higher-speed streets typically associated with the highest injury severity for pedestrians.For those higher-speed streets, redesigning them to communicate lower speed, such as through a roadway-reconfiguration effort, can effectively accomplish the goal of lowering speed. In the absence of street redesign, however, another effective current solution is enforcement, and particularly automated speed enforcement (ASE) that frees police to focus on other issues and that is free from implicit or explicit bias. It is important to carefully consider community context when selecting locations to employ ASE, to avoid disproportionately burdening any historically disadvantaged communities that surround the typically high-speed streets that need to be addressed.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 535: Pedestrian Safety Relative to Traffic-Speed Management aims to document what is known about strategies and countermeasures to address pedestrian safety via traffic-speed management in urban environments. For example, the City of San Francisco regularly uses curb extensions as traffic-calming devices on its streets. However, the political and land use context of each city heavily influences the types of treatments that are considered feasible for each city. Thus, the City of Los Angeles has had to find alternatives to both ASE and road diets, the latter of which have been the subject of intense public backlash in some cases.These realities—that speed management can be fraught with difficulty—have spurred creative thinking about how to work within contextual confines, resulting in some particularly noteworthy and promising practices. For example, the City of Nashville anticipated potential backlash against speed-management efforts and thus chose to work with advocacy groups to identify areas of the city desiring walkability improvements. By installing walkability improvements in those areas first, city leaders created instant wins that could be used as leverage for future projects.The authors of the synthesis found there may be a need for greater clarity about the speed-limit-setting process, as well as for greater collaboration between local and state agencies when state roads run through urban areas. In particular, it may be worth exploring whether there is a need for a framework that will foster collaboration between local and state staff on safety initiatives such as achieving flexibility in roadway design, changing laws or regulations that govern speed-limit setting, and finding a balance between local safety needs and regional mobility needs. Such a framework may support both local and state agencies attempting to address safety issues and reach larger goals as articulated through movements like Vision Zero.
Keywords: Transportation and Infrastructure

Very Short Duration Work Zone Safety for Maintenance and Other Activities - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 533 identifies the current state of practice among state departments of transportation (DOTs) regarding selection and setup of very short duration work zone (VSDWZ).The report presents case examples of four state DOTs along with an in-depth analysis of the VSDWZ policies of these states. The case example agencies have developed specific guidance on the topic for their jurisdictions.VSDWZ activities are those activities not defined in the Manual on Uniform Traffic Control Devices (MUTCD) under short duration work zone or temporary traffic control (TTC) zones. These activities are usually 1 to 20 minutes long and include maintenance activities (e.g., performing temporary patching, picking up debris, or placing traffic count tubes) where TTC is not set up.VSDWZ activities reduce the exposure of workers to risk and the inconvenience to traffic that standard TTC zones would create. Current policies and practices in place at various agencies for VSDWZ activities vary substantially. The work-zone setup also varies by the type of maintenance or other very short duration activity and roadway classification (e.g., speed, AADT, and number of lanes). Historically, during those activities, a large number of worker fatalities have occurred.
Keywords: Transportation and Infrastructure

Report Series: Committee on Astrobiology and Planetary Science: Review of the Commercial Aspects of NASA SMD's Lunar Science and Exploration Initiative - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On December 11, 2017, President Donald Trump signed Space Policy Directive-1 (SPD-1). The new directive replaced original text in the National Space Policy of the United States of America and instructed the Administrator of the National Aeronautics and Space Administration (NASA) to "lead the return of humans to the Moon for long-term exploration and utilization, followed by human missions to Mars and other destinations".
Keywords: Space and Aeronautics

Review of the Bureau of Ocean Energy Management "Air Quality Modeling in the Gulf of Mexico Region" Study - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Emissions associated with oil and gas exploration, development, and production on the Gulf waters can result in increased levels of air pollutants that contribute to a range of air quality impacts in the Gulf of Mexico Region (GOMR). “Criteria air pollutants”, such as carbon monoxide, lead, nitrogen dioxide, ozone, particulate matter, and sulfur dioxide, are considered harmful to public health and the environment. The Bureau of Ocean Energy Management (BOEM) manages the U.S. outer continental shelf oil and gas resources and is required to help manage air quality in the GOMR.
Keywords: Environment and Environmental Studies; Earth Sciences

Report Series: Committee on Astrobiology and Planetary Science: Review of the Planetary Science Aspects of NASA SMD's Lunar Science and Exploration Initiative - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On December 11, 2017, President Donald Trump signed Space Policy Directive-1 (SPD-1). The new directive replaced original text in the National Space Policy of the United States of America and instructed the Administrator of the National Aeronautics and Space Administration (NASA) to “lead the return of humans to the Moon for long-term exploration and utilization, followed by human missions to Mars and other destinations”.
Keywords: Space and Aeronautics

Artificial Intelligence Applications for Older Adults and People with Disabilities: Balancing Safety and Autonomy: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On October 24, 2018, the National Academies of Sciences, Engineering, and Medicine held a workshop titled Artificial Intel¬ligence Applications for Older Adults and People with Disabilities: Balancing Safety and Autonomy. This workshop examined the state of the art and knowledge about artificial intelligence and explored its potential to foster a balance of safety and autonomy for older adults and people with disabilities who strive to live as independently as possible. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Leveraging Private Capital for Infrastructure Renewal - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Public–private partnerships (P3s) can provide solutions to the project delivery challenges faced by state departments of transportation (DOTs) and local transportation agencies in delivering surface transportation infrastructure by aligning risks and rewards between public and private sectors, accelerating project delivery, improving operations and asset management, realizing construction and operational cost savings, and attracting private-sector equity investment.P3s are becoming an increasingly important option for financing and implementing critical improvements to U.S. surface transportation infrastructure. As interest in P3s grows, U.S. transportation agencies and stakeholders evaluating the potential benefits of P3s have raised issues relating to the role of private equity in these transactions.Recognizing the complexity and challenges of structuring a highway or bridge P3 compared to a conventional procurement, the objective of NCHRP Synthesis 540: Leveraging Private Capital for Infrastructure Renewal is to bridge the knowledge gap on the role of equity in surface transportation P3 projects and to document current practices relating to private-equity investments in small-scale and large-scale transportation infrastructure projects.
Keywords: Transportation and Infrastructure

Toward New Naval Platforms: A Strategic View of the Future of Naval Engineering - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. Navy has many unique naval engineering needs that demand a highly capable and robust U.S. naval engineering enterprise. In seeking an independent review of the unclassified elements of its National Naval Responsibilities—Naval Engineering (NNR-NE) program, the Office of Naval Research (ONR) asked for recommendations on ways to ensure the program meets the many naval engineering research, education, and workforce needs that will be critical to the Future Navy. Toward New Naval Platforms: A Strategic View of the Future of Naval Engineering recommends a number of strategies, including advice that ONR adopt a “lead, leverage, and monitor” framework for the programming, prioritization, and integration of its investments within and across the NNR-NE’s three “pillars” of science and technology (S&T), education and workforce development, and experimental infrastructure. The report points out that as the technological landscape critical to naval engineering continues to expand at a rapid pace, NNR-NE must make strategic choices about when it should invest directly in research that meets naval-unique S&T needs, and when it should leverage technological advances from other domains.Likewise, the report points to the importance of the NNR-NE making direct investments to inspire STEM interest among K-12 students and attract undergraduate and graduate students to the field of naval engineering but also to leverage the many STEM programs found elsewhere in the Navy and Department of Defense.The report stresses the importance of engaging individuals from under-represented groups to expand the naval engineering talent pool and to find creative ways to expedite the recruitment of workers to Navy-critical professions by providing naval engineering graduates with early work opportunities while awaiting security clearances.
Keywords: Transportation and Infrastructure

Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB Special Report 329: Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future explores pending and future federal investment and policy decisions concerning the federal Interstate Highway System. Congress asked the committee to make recommendations on the “features, standards, capacity needs, application of technologies, and intergovernmental roles to upgrade the Interstate System” and to advise on any changes in law and resources required to further the recommended actions. The report of the study committee suggests a path forward to meet the growing and shifting demands of the 21st century.The prospect of an aging and worn Interstate System that operates unreliably is concerning in the face of a vehicle fleet that continues to transform as the 21st century progresses and the vulnerabilities due to climate change place new demands on the country’s transportation infrastructure. Recent combined state and federal capital spending on the Interstates has been about $20–$25 billion per year. The estimates in this study suggest this level of spending is too low and that $45–$70 billion annually over the next 20 years will be needed to undertake the long-deferred rebuilding of pavements and bridges and to accommodate and manage growing user demand. This estimated investment is incomplete because it omits the spending that will be required to meet other challenges such as boosting the system’s resilience and expanding its geographic coverage.The committee recommends that Congress legislate an Interstate Highway System Renewal and Modernization Program (RAMP). This program should focus on reconstructing deteriorated pavements, including their foundations, and bridge infrastructure; adding physical capacity and operations and demand management capabilities where needed; and increasing the system’s resilience. The report explores ways to pay for this program, including lifting the ban on tolling of existing general-purpose Interstate highways and increasing the federal fuel tax to a level commensurate with the federal share of the required RAMP investment.View the videos, recorded webcast, graphics, summary booklet, press release, and highlights page at interstate.trb.org.
Keywords: Transportation and Infrastructure

Guidebook for Developing a Comprehensive Renewable Resources Strategy - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB's Airport Cooperative Research Program (ACRP) Research Report 197: Guidebook for Developing a Comprehensive Renewable Resources Strategy highlights renewable energy sources, includes steps for developing a renewable energy strategy, and identifies metrics for measuring success. The report also highlights real-world examples of successful renewable resource projects at airports.Renewable resources to reduce emissions from airports and climate impacts have been discussed for several years. Technological advancements have allowed organizations, specifically airports, to begin integrating renewable resources into their overall energy plans. In an effort to address climate impacts and achieve neutral carbon growth by 2020, a coalition of aviation stakeholders has adopted emission reduction targets.Airports are also seeking to become energy independent, and using renewable resources as a strategy to get there. Further, as the costs for conventional energy sources increases, renewable resources become more financially attractive. Those airports who have implemented renewable resources have been able to do so at minimal cost.While a business case can be made for the integration of any one particular renewable resource, an airport can be more strategic by adopting an overall renewable resource strategy. The renewable resources strategy can then become an input to other airport planning documents (e.g., airport master plan, strategic plan). The success of developing the plan as well as implementation require all internal and external stakeholders are involved in the process.
Keywords: Transportation and Infrastructure